Comparative Analysis of Postmortem Biochemical Markers in Vitreous Humor and Cerebrospinal Fluid for Estimating Time of Death - Farhat Sultana, Khalid Mahmood, Riasat Ali, Fariha Tariq, Zubia Iqbal, Aatiqa Abbas, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Forensic investigations in Pakistan that have climatic diversity require accurate estimation of postmortem interval (PMI). Environmental variability makes traditional physical methods unreliable, and as a result biochemical methods using postmortem fluids are used. Objective: This study aimed to compare the efficacy of vitreous humor and cerebrospinal fluid (CSF) biochemical markers as complementary tools in the estimation of PMI in a forensic setting. Methods: n=60 medico-legal autopsy cases were studied prospectively in the Forensic Medicine Departments of Jinnah hospital and Mayo hospital, Lahore, Pakistan. Minimal decomposition and lack of confounding ocular or CNS pathologies were ensured by inclusion and exclusion criteria. CSF and vitreous humor samples were obtained at autopsy within 12 hours postmortem. Vitreous humor potassium, glucose, and lactate levels were measured with ion-selective electrodes, and CSF levels of neuron-specific enolase (NSE) and S100B were determined by ELISA. Ambient temperature and humidity were used as covariates in statistical analyses, including Pearson correlation and multiple linear regression. Results: Vitreous potassium had a strong positive correlation with PMI (r = 0.85, p < 0.001), explaining 72% of the variance in PMI. The level of S100B was not statistically significant while CSF NSE moderately correlated with an R² value of 0.45 (r = 0.68, p = 0.002). These results demonstrate that vitreous potassium is a superior predictor of PMI than CSF markers, which provide complementary information on central nervous system degradation. Conclusions: The results support the use of vitreous humor as the primary fluid for biochemical PMI estimation with CSF markers being useful adjuncts, especially in cases of CNS pathology. Forensic time of death determinations in Pakistan may be improved with a dual fluid approach adjusted for local environmental conditions. Keywords: Postmortem Interval, Vitreous Humor, Cerebrospinal Fluid, Biochemical Markers, Forensic Science, Pakistan